Globalization and Chinese Buddhism: The Canadian experience - Liu, Tannie (University of Ottawa (Canada), 2004)
This thesis examines three major Chinese Buddhist temples in Toronto, Montreal and Ottawa and argues that the local manifestations of these Chinese temples cannot be understood simply as devices developed by immigrants in order to adapt to Canadian life. Rather, they are part of transnational movements within Chinese Buddhism which are geared to the global migration of the religion in the context of a competition between different ideologies. The thesis, therefore, argues that the development of these temples cannot be understood without situating them within a global context and examining the social and historical developments that led to the modern transformation of Chinese Buddhism. The contemporary form of Chinese Buddhism is to a large extent a response to the challenge placed on Buddhism by the globalization process. This process led to a significant influx of foreign ideologies and religious practices into China---such as Marxism, modern positivistic science, and in particular Christianity. This juxtaposition of different ideologies in China in the early part of the twentieth century posed a severe challenge to Chinese Buddhism and inspired some of the religious leaders to initiate reforms. The thesis also argues that religious identity in the contemporary world, when religious institutions are stripped from their traditional authority and total support from the government, has to be continuously negotiated within the global context. This ongoing negotiation produces change. However, the thesis also argues that certain ideological aspects within a culture are perceived as sacred, and this will tend to buffer the culture to some extent in its responses to outside influences. For instance, the belief in Taoism within Chinese culture has withstood Chinese openness to Buddhism, Christianity, Marxism and positivistic science. This constant renegotiation process within a particular culture and the larger group culture can best be described in Roland Robertson's terms as the interpenetration of the local and the global, a continuous give and take between the cultural and universal models. This thesis concludes that the three temples under investigation---that is, the Cham Shan Temple in Toronto, the Fo Guang Shan Temple in Ottawa, and the True Buddha School in Montreal, reflect the transformation of Buddhism due to the historical and social developments in China. The temples are differently established on each of these three sites due to the different orientations of the founders to various global influences, and in turn cater to different needs and preferences of Chinese immigrants in Canada.
Keywords: Religion, General.